Deciduous tooth early loss prevalence in posterior region and indication of band-loop space maintainer - De lira, Ana de Lourdes Sá; Costa, Ageu Lima da; Fonseca, Guilherme Henrique Alves da; Silva, Nayra Rafaelle Fernandes da; Martins, Keila Rejane de Jesus (Brazilian Dental Science, 2019)
Aim: To investigate the prevalence of the early unitary loss of deciduous and the need for space maintainer in the posterior region, of the band-loop type. Methods: The clinical examination of 568 children between 6 and 12 years of age in mixed dentition was performed in two municipal schools. After the diagnosis of premature loss of one or two deciduous molars (unilateral, one or both arches, respectively), without successors initiating the eruptive process in the oral cavity, the child was referred to the Clinical School of Dentistry of UESPI (CSD ) for installation of the band-handle space maintainer. Results: The prevalence of early molar loss was 4.04%, the etiological factor of which was dental caries for all sample. Only 13 attended the CEO for detailed examination. After radiographic examination, it was verified that 8 did not need space maintainers because they were approximately 2/3 of the permanent successors root formation. In 5 children was placed the maintainer of space, band-handle, who are being supervised every 3 months until the eruption of the permanent successors. Conclusion: The prevalence of early premolar molar loss was 4.04% with no statistical difference between genders. The use of space maintainers after the early loss of a deciduous tooth is a preventive measure of malocclusion, being the band-loop appliance an excellent choice after loss of the deciduous unilateral molar.